Algorithm for the implementation of management decision support in agricultural production - et. al., Yu.Q. Qutlimuratov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article application the implementation of an algorithm for making management decisions on alternative options for solving the two-criterial ecological-economic model of location and specialization of agricultural production.